Resolution : Issue n° 0 : The Pixel. - Otto, Laurens
Beerts, Jonas ; Boerman, Doris ; Cleutjens, Caszimir ; Denil, David ; Heuninck, Elias ; Lignou-Tsamantani, Kyveli ; Manovich, Lev ; Mercuriali, Giacomo ; Mitchell, William J. ; Smith, Alvy Ray
boek